2014
DOI: 10.1007/s10803-014-2087-9
|View full text |Cite
|
Sign up to set email alerts
|

Group Cognitive Behavioural Therapy Program Shows Potential in Reducing Symptoms of Depression and Stress Among Young People with ASD

Abstract: We examined the efficacy of cognitive behavioural therapy (CBT) delivered in groups on the reduction of symptoms of depression, anxiety and stress in young people on the autism spectrum. Utilising a quasi-experimental design, comparisons were made between individuals allocated to a group intervention program and individuals allocated to a waitlist. Following the intervention program, participants who were initially symptomatic reported significantly lower depression and stress scores on the Depression Anxiety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 40 publications
2
75
0
Order By: Relevance
“…Although it is often assumed that CBT (with more general, rather than anxiety-specific, protocols) would also be beneficial to treat depression in ASD, there is limited direct evidence for this assumption. Interestingly, a recent quasi-experimental design of group CBT with adolescents and young adults with ASD found that depression improved whereas anxiety did not [27]. …”
Section: Treatment Of Anxiety and Depression Asdmentioning
confidence: 99%
“…Although it is often assumed that CBT (with more general, rather than anxiety-specific, protocols) would also be beneficial to treat depression in ASD, there is limited direct evidence for this assumption. Interestingly, a recent quasi-experimental design of group CBT with adolescents and young adults with ASD found that depression improved whereas anxiety did not [27]. …”
Section: Treatment Of Anxiety and Depression Asdmentioning
confidence: 99%
“…This is a more experiential approach than actively targeting and arguing with thoughts, and it may be easier for people with ASD to utilize (Mazefsky & White, 2014). In fact, mindfulness techniques are even being incorporated in new CBT protocols for people with ASD (McGillivray & Evert, 2014).…”
Section: Emotional Acceptancementioning
confidence: 99%
“…antidote to noxious thoughts; Sofronoff et al 2005) • Use of idiosyncratic rating scales such as James and the Maths test and a feelings thermometer to concretely measure change instead of asking about feelings directly • Incorporate a relaxation strategy section into the programme to support affect management concretely • Tangible reinforcement programme in session which can be translated to home and school such as a token reinforcement programme • Use of video modelling and role play to teach coping strategies • Increased use of games to convey concepts and maintain interest for younger children • Employ an additional parenting component to teach parents about the role of overprotective parenting in anxiety disorders and strategies to support their child and manage their own feelings of anxiety • Link with schools to increase school-based support and generalisation of concepts Depression Only one study was identified which met the eligibility criteria for the current study for treating depression in young people with ASD. McGillivray and Evert (2014) recruited 32 high functioning participants (23 males) from a community sample aged between 15 and 25 years, diagnosed with Asperger's syndrome (n = 23) and HFA (n = 9), through community-based advertisements. ASD diagnosis was confirmed with a telephone interview only, and the presence of depression was determined through a self-report questionnaire (Depression Anxiety Stress Scales) indicating poor representativeness and validation of case definition.…”
Section: Obsessive-compulsive Disordermentioning
confidence: 99%